DAMPAK DAN PERLINDUNGAN HUKUM AKIBAT TERJADINYA PENGGABUNGAN PERUSAHAAN (MERGER) TERHADAP KARYAWAN - Aris Munandar; Rani Apriani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
Companies usually decide to merge with the aim of increasing the variety of business fields, funds, the level of efficiency of company management, to liquidity. Although a merger can bring many advantages, it also has some negative effects that can occur. Especially for the parties in the company. One of them is the employee. The problems that will be studied by the author in this study are: 1). What is the impact of the merger on employees; 2). How is the legal protection due to the merger of companies (merger) for employees. This research is a normative juridical research. The results of this study conclude that the impact of the merger for employees is that layoffs can occur which are very detrimental. Therefore, legal protection must be given to employees to ensure justice for them. Keywords: Merger; Impact and Legal Protection; Employee.